The effects of a reduced fractional inspired oxygen concentration on ventilation and A-a oxygen gradient in isoflurane anesthetized horses - Crumley, Mariana Neubauer (Kansas State University, 2011)
Hypoventilation (PaCO2 > 45 mmHg) and large P(A-a)O2 gradients due to V/Q mismatch and shunt, are common during isoflurane anesthesia in horses. A fraction of inspired oxygen < 50% has been shown to improve ventilation and decrease intra-operative atelectasis in humans and some animals. The study compared the effects of two different fractions of inspired oxygen, 50% versus > 95%, on ventilation, respiratory pattern, and P(A-a)O2 gradient in isoflurane anesthetized horses. Eight mature horses were sedated with IV xylazine (1.0 mg/kg) and anesthetized with diazepam (0.05 mg/kg) and ketamine (2.2 mg/kg) twice. Anesthesia was maintained with isoflurane (ET1.5 vol%) in either 50 or > 95% oxygen for 90 minutes. Both treatments were randomly assigned to each horse with a one week interval in between treatments. Horses were positioned in dorsal recumbency, connected to a preloaded circle breathing system and allowed to spontaneously ventilate. Measurements included inspiratory and expiratory peak flow and time, tidal volume, respiratory frequency, ETCO2, CO2, O2, PaO2, PaCO2, pH, SaO2, heart rate, and arterial blood pressure. Calculated values included PAO2, P(A-a)O2, P(A-a)O2 rate of change, and physiologic dead space. FiO2 of 50% resulted in a lower PaO2, SaO2, PAO2, and P(A-a)O2. No significant change in PaCO2, ventilatory pattern, or any remaining measured variables was observed (p<0.05). The use of 50% oxygen and nitrogen as the carrier gas did not significantly change the ventilatory characteristics or improve oxygenation in isoflurane anesthetized horses. Repeatable respiratory rhythms characteristics were observed for horses while inspiring 50% and > 95% oxygen. A high A-a oxygen gradient with an equal rate of change overtime was still observed during both treatments.
Keywords: Equine anesthesia; Inspired oxygen concentration; Ventilatory characteristic; A-a oxygen gradient; Veterinary Medicine (0778)